IFRS ADOPTION AND VALUE RELEVANCE OF ACCOUNTING INFORMATION OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA - Para, Ibrahim; Bala, Husseini; Khatoon, Ghousia; Karaye, Abubakar; Abdullah, Hariem (Humanities Journal of University of Zakho, 2022)
The study examines the effect of IFRS adoption on the value relevance of accounting information of six (6) out of thirteen (13) listed industrial goods firms in Nigeria for the period of fourteen years (2007-2020); seven (7) years before IFRS adoption and seven (7) years after IFRS adoption. Earnings per share (EPS), Book value per share (BVPS) and Dividend per share (DPS) constitute the independent variables and share price as the dependent variable. Ex-post facto research design was employed and multiple regression models as well as Ohlson (1995) price model were used to analysis the audited financial statement of the sample size. The result reveal that EPS is negatively and DPS is positively associated with share price and both are significant, while BVPS is insignificantly associated with share price in the pre-IFRS era. On the other hand, EPS has negative significant association with share price, while BVPS and DPS is having a positive and significant association with share price in the post-IFRS era. Therefore, it is concluded that the value relevance of accounting information has increase after the adoption of IFRS; this is supported by the R2of post-IFRS (51%) which is higher than the R2of pre-IFRS (30%)